1996
DOI: 10.1007/bf02352301
|View full text |Cite
|
Sign up to set email alerts
|

Geosiphon pyriforme, a fungus forming endocytobiosis withNostoc (Cyanobacteria), is an ancestral member of the glomales: Evidence by SSU rRNA Analysis

Abstract: Geosiphon pyriforme inhabiting the surface of humid soils represents the only known example of endocytobiosis between a fungus (Zygomycotina; macrosymbiont) and cyanobacteria (Nostoc; endosymbiont). In order to elucidate the taxonomical and evolutionary relationship of Geosiphon pyriforme to fungi forming arbuscular mycorrhiza (AM fungi), the small-subunit (SSU) ribosomal RNA genes of Geosiphon pyriforme and Glomus versiforme (Glomales; a typical AM fungus) were analyzed and aligned with SSU rRNA sequences of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
88
2
2

Year Published

2000
2000
2017
2017

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 165 publications
(98 citation statements)
references
References 37 publications
4
88
2
2
Order By: Relevance
“…The phylogenetic and taxonomic status of the muco-ralean family Mortierellaceae is problematic because it appeared to be distantly related to the other mucoralean fungi, i.e., it rather clusters with Endogone in several nSSU rDNA studies (Gehrig et al, 1996;Jensen et al, 1998). Besides molecular data, Mortierellacean fungi possess several characteristic phenotypic and biochemical properties that are distinct from other mucoralean fungi: hyaline and smooth zygospores, sporangia without a columella (a structure inside the sporangium that is extended from the sporangiophore), and desmosterol and 24,25-methylene cholesterol as the major sterol components (ergosterol in other mucoralean fungi; see Gandhi, 1997, 1999).…”
Section: Relationships Within Zygomycotamentioning
confidence: 99%
See 2 more Smart Citations
“…The phylogenetic and taxonomic status of the muco-ralean family Mortierellaceae is problematic because it appeared to be distantly related to the other mucoralean fungi, i.e., it rather clusters with Endogone in several nSSU rDNA studies (Gehrig et al, 1996;Jensen et al, 1998). Besides molecular data, Mortierellacean fungi possess several characteristic phenotypic and biochemical properties that are distinct from other mucoralean fungi: hyaline and smooth zygospores, sporangia without a columella (a structure inside the sporangium that is extended from the sporangiophore), and desmosterol and 24,25-methylene cholesterol as the major sterol components (ergosterol in other mucoralean fungi; see Gandhi, 1997, 1999).…”
Section: Relationships Within Zygomycotamentioning
confidence: 99%
“…Several nSSU rDNA studies have suggested that the Glomales evolved separately from other basal fungal orders, and that it was related to even higher fungi (Bruns et al, 1992;Gehrig et al, 1996;Jensen et al, 1998;Nagahama et al, 1995;Schüßler et al, 2001). From these results, Schüßler et al (2001) revised the higher-level taxonomy of the Glomales: the Glomales (sensu Morton and Benny, 1990) was elevated to the new phylum Glomeromycota, and the four orders, the Archaeosporales, Diversisporales, Glomerales, and Paraglomales were revised or newly erected within the Glomeromycota.…”
Section: Relationships Within Zygomycotamentioning
confidence: 99%
See 1 more Smart Citation
“…Difficulties persist in the identification and nomenclature of mycobionts, requiring a combination of morphological, physiological and molecular approaches (Jorgensen, 1991 ;Gargas & Taylor, 1992 ;Bridge & Hawksworth, 1998 ;Nimis, 1998 ;Rambold et al, 1998). †See Schussler et al (1994) and Gehrig et al (1996). ‡See Villareal (1992), Schenk (1992) and Carpenter et al (1999).…”
Section: Hosts and Their Rolementioning
confidence: 99%
“…AM fungi predominantly belong to the phylum Glomeromycota (Gehrig et al, 1996;Schussler et al, 2001). They enhance water uptake and mineral nutrition (mostly inorganic phosphate [P i ]) of the host plant, which, in return, provides photosynthates to the fungus through hyphal structures called arbuscules (Baier et al, 2010;Doidy et al, 2012).…”
mentioning
confidence: 99%